Architecture and Philosophy: Reflections on Arakawa and Gins - Jondi Keane; Evan Selinger (Footprint)
This essay is a critical review of a recent Arakawa and Gins conference – an event that brought phenomenology and architecture into productive dialog through the advancement of interdisciplinary inquiry into the subtle and complex ways that embodied activity structures cognition and perception. To provide the reader with sufficient context to appreciate the ensuing discussion of Arakawa and Gins’s concepts and hypotheses, we open with an overview of their previous collaborations. We then transition to analysis of a unique installation called 'Reading Room', and, immediately afterwards, provide exegetical commentary on select conference presentations. This commentary emphasizes phenomenological perspectives, especially ideas that Don Ihde and Shaun Gallagher conveyed. We conclude by outlining some of the most promising horizons of thought that the conference brought to our consideration.